Mid-Late Holocene Paleoenvironmental and Sea Level Reconstruction on the Al Lith Red Sea Coast, Saudi Arabia - Ghandour, Ibrahim M.; Al-Zubieri, Aaid G.; Basaham, Ali S.; Mannaa, Ammar A.; Al-Dubai, Talha A.; Jones, Brian G. (Frontiers in Marine Science, 2021)
Late Quaternary paleoenvironments are of particular interest to understand how the Earth System's climate will respond to the undramatic changes during this period, compared with the broader glacial-interglacial variations. In this study, a shallow sediment core (2.84 m long) retrieved from the Red Sea coastal zone in northern Ghubbat al Mahasin, south of Al-Lith, Saudi Arabia, is used to reconstruct the mid-Late Holocene paleoenvironments and sea level based on a multiproxy approach. Remote sensing data, sedimentary facies, benthic foraminiferal assemblages, δ18O and δ13C stable isotopes, and elemental composition and 14C dating were utilized. The stratigraphy of the core shows three distinctive depositional units. The basal pre 6000 yr BP unit consists of unfossiliferous fine to medium sand sharply overlain by black carbonaceous mud and peat, suggesting deposition in a coastal/flood plain under a warm and humid climate. The middle unit (6000-3700 yr BP) records the start and end of the marine transgression in this area. It consists of grey argillaceous sand containing bivalve and gastropod shells fragments and a benthic foraminiferal assemblage attesting a lagoonal or quiet shallow marine environment. The upper unit (<3700 yr BP) consists of unfossiliferous yellowish-brown argillaceous fine-grained sands deposited on an intertidal flat. Both middle-and upper-units stack in a regressive shallowing upward pattern although they may be separated by a hiatus. The overall regressive facies and the stable isotopic data are consistent with a late Holocene sea-level fall and a change to a more arid climate.